AN EXPERIENTIAL STUDY ON THE PRACTICAL APPLICATION OF INCOME TAX AND GST COMPLIANCE IN INDIA - Kavya. P; Sah, Jyoti; Sharma, Bhawna (International Journal of Research -GRANTHAALAYAH, 2025)
This research paper presents an experiential study bridging the gap between theoretical taxation knowledge and its practical application in India’s compliance framework based on observations from a six-week internship at a chartered accountancy firm. The study connects theoretical taxation concepts with their real-world application by examining activities such as return preparation, verification, documentation, reconciliation and filing across Income Tax, GST and TDS. A descriptive and experiential research design was adopted using primary data from workplace participation and secondary data from government portals and professional publications. The findings show that digital tools like Computax, Tally ERP and statutory portals enhance accuracy, efficiency and transparency while reducing the manual errors. Challenges include portal glitches, frequent policy updates, limited access to sensitive data and delays in client submissions. The study concludes that effective tax compliance depends on clear processes, proper documentation, ethics and technology use, offering useful insights for researchers and tax professionals.